2004
DOI: 10.1128/cmr.17.4.1012-1030.2004
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Immune Activation Associated with Chronic Helminthic and Human Immunodeficiency Virus Infections: Role of Hyporesponsiveness and Anergy

Abstract: Chronic immune activation is one of the hallmarks of human immunodeficiency virus (HIV) infection. It is present also, with very similar characteristics, in very large human populations infested with helminthic infections. We have tried to review the studies addressing the changes in the immune profiles and responses of hosts infected with either one of these two chronic infections. Not surprisingly, several of the immune derangements and impairments seen in HIV infection, and considered by many to be the “spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
164
1
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(178 citation statements)
references
References 262 publications
(288 reference statements)
10
164
1
3
Order By: Relevance
“…The present research extended this knowledge by showing that there was no association between TST results and low versus high helminth egg burden or co-infections with multiple helminth species. Also, in contrast with other studies in communities with a high prevalence of intestinal helminths, we found no participants with completely unreactive TST, 21,22 despite almost universal intestinal helminth infections and frequent co-infections with multiple intestinal helminths. Potential explanations for this include the likely lifelong helminth infections in the indigenous community in the present research.…”
Section: Discussioncontrasting
confidence: 54%
“…The present research extended this knowledge by showing that there was no association between TST results and low versus high helminth egg burden or co-infections with multiple helminth species. Also, in contrast with other studies in communities with a high prevalence of intestinal helminths, we found no participants with completely unreactive TST, 21,22 despite almost universal intestinal helminth infections and frequent co-infections with multiple intestinal helminths. Potential explanations for this include the likely lifelong helminth infections in the indigenous community in the present research.…”
Section: Discussioncontrasting
confidence: 54%
“…Few studies have reported the relationship between cytokines in individuals with HIV and parasitic intestinal infections. Some authors evaluated cytokines and their relationship with parasites such as Schistosoma mansoni, Wuchereria bancrofti, and Trichinella spiralis (71)(72)(73)(74)(75)(76)(77)(78)(79). No correlation between serum INF-γ, IL-2, and IL-10 levels and intestinal parasitic infections was seen.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic infl ammation from helminth infection results in immune dysregulation and reduction in CD4 T-cell count 10,11,12 . This was corroborated in index study where prevalence rates of helminth infection were highest in subjects with advanced and severe immunodefi ciency stages of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Many helminth parasites are long-lived and cause chronic infections 8,9 . Chronic helminth infestation was reported to cause immune dysregulations, characterized by a dominant Th2 type of cytokine immune response (predominantly IL-4 and IL-5, IL-10), a high IgE levels, eosinophilia, low CD4+ and a high CD8+ cells count 10,11,12 .…”
mentioning
confidence: 99%